THE COST-EFFECTIVENESS OF PHARMACEUTICAL CARE TO SLOW PROGRESSION OF THE KIDNEY IN CHRONIC KIDNEY DISEASE WITH DIABETES PATIENTS AT LAEM CHABANG HOSPITAL, CHONBURI PROVINCE - PATTANAMONGKOL, ORATHAI; CHANTARACHA, DUSIT; CHALONGSUK, RAPEEPUN; PONGCHAIDECHA, MANAT; RUNGPRAI, DARAPORN; MUONGMEE, SUTHABORDEE (Thai Bulletin of Pharmaceutical Sciences, 2018)
การศึกษานี้เป็นการวิจัยเชิงทดลองแบบสุ่ม เพื่อเปรียบเทียบความคุ้มค่าของการให้บริบาลเภสัชกรรมต่อการชะลอการเสื่อมของไตในผู้ป่วยนอกโรคไตเรื้อรังร่วมกับโรคเบาหวาน เก็บข้อมูลในเดือน เมษายน 2559 - มีนาคม 2560 จำนวนผู้ป่วย 168 ราย แบ่งเป็นกลุ่มที่ได้รับการให้บริบาลทางเภสัชกรรม (structured care; SC) 83 ราย และกลุ่มระบบปกติ (usual care; UC) 85 ราย ผลการเปรียบเทียบการเปลี่ยนแปลงค่า eGFR ที่เพิ่มขึ้น และค่าระดับแอลบูมินในปัสสาวะที่ลดลงของผู้ป่วยทั้งสองกลุ่มไม่มีความแตกต่างกัน (p = 0.73, p = 0.08) แต่กลุ่ม SC พบจำนวนปัญหาและการแก้ไขปัญหาที่เกิดจากการใช้ยามากกว่ากลุ่ม UC (ร้อยละ 58.89, 43.18) การประเมินต้นทุนประสิทธิผลของกลุ่ม SC มีต้นทุนรวม 215,016 บาท ต้นทุนเฉลี่ย 2,590.55 บาทต่อราย ส่วนกลุ่ม UC มีต้นทุนรวม 198,822 บาท ต้นทุนเฉลี่ย 2,339.08 บาทต่อราย กลุ่ม SC และกลุ่ม UC มีอัตราส่วนต้นทุนต่อประสิทธิผลจำนวนผู้ป่วยที่มีการเปลี่ยนแปลงของค่า eGFR คงที่หรือเพิ่มขึ้น (4,134.92 และ 4,142.13) ต้นทุนต่อประสิทธิผลจำนวนผู้ป่วยที่มีการเปลี่ยนแปลงของค่าระดับแอลบูมินลดลง (3,359.63 และ 4,142.13) จากการวิเคราะห์อัตราส่วนต้นทุนต่อประสิทธิผลส่วนเพิ่ม กลุ่ม UC เมื่อเปลี่ยนมาเป็นกลุ่ม SC ต้องใช้ทุนเพิ่มขึ้นต่อการเพิ่มจำนวนผู้ป่วยให้มีการเปลี่ยนแปลงของค่า eGFR คงที่หรือเพิ่มขึ้น 1 ราย จำนวนผู้ป่วยที่มีการเปลี่ยนแปลงของค่าระดับระดับแอลบูมินลดลง 1 ราย และจำนวนการค้นหาและแก้ไขปัญหาที่เกี่ยวข้องกับการใช้ยาเพิ่มขึ้น 1 ปัญหา (4,048.5 บาทต่อราย, 1,012.13 บาทต่อราย และ 108.62 บาทต่อปัญหา) โดยสรุปการให้บริบาลทางเภสัชกรรมร่วมกับทีมสหสาขาวิชาชีพมีความคุ้มค่าสามารถชะลอไตเสื่อมได้ This study was a randomized control trial to compare the cost-effectiveness of pharmaceutical care on delaying the progression of renal insufficiency among patients with CKD and Type 2 diabetes at Laem Chabang Hospital. The data were collected from April, 2016 to March, 2017. Eligible patients (n = 168) were randomly allocated to either the structured care (SC) group (n = 83) or the usual care (UC group (n = 85). The results showed that the estimated glomerular filtration rate and urine albuminuria values in both SC and UC groups were not statistically significant (p = 0.73, p = 0.08), but in the SC group greater numbers of DRPs were found and solved (58.89, 43.18 percent). The results of the cost-effectiveness analysis showed that the total cost of the SC group was 215,016 Baht with an average cost of 2,590.55 Baht per case. Meanwhile, the total cost of the UC group was 198,822 Baht with an average cost of 2,339.08 Baht per case. The SC group and UC group showed a cost-effectiveness ratio considering the number of patients with constant or increased eGFR changes of 4,134.92 and 4,142.13 respectively, and when considering the number of patients with decreased ACR changes, the values were 3,359.63 and 4,142.13 respectively. The results of incremental cost-effectiveness ratio showed that when effectiveness was measured by the number of patients with constant or increased eGFR changes, the number of patients with decreased ACR changes and the number of DRPs found and solved, the figures were 4,048.5 Baht/patient, 1,012.13 Baht/patient and 108.62 Baht/DRP respectively. In conclusion, the pharmaceutical care program with the multidisciplinary team was more cost-effective in delaying the progression of renal insufficiency.